Keynote: Food as Delineator in Dinner Rush: A Semiotic of Generational Difference among “Italians” in America - Tamburri, Anthony Julian (E|C, 2020)
Like other films dealing with food, Bob Giraldi’s Dinner Rush (2000) bespeaks and hence discusses food as both identity marker and indicator for shifts in generational dynamics among Italians in America, especially between father and son. My use of the term “Italians in America” encompasses those who were born and raised in Italy, and who then moved to the United States, and, as well, those who are descendants of Italian immigrants. Dinner Rush also deals with the identity of Italians in America as members of organized crime, this too a signifier for generational difference and, we might also say, food. Hence, I have in mind the famous scene in The Godfather (1972) when Clemenza gives Michael a quick lesson in making pasta sauce, or, even later, the scene in Goodfellas (1989) where Paulie is preparing dinner while in jail, carefully slicing and dicing garlic with a razor blade. These are just two of a plethora of scenes in American films that include indelible Italian/American food scenes.